The macroeconomics of development finance: A Kaleckian analysis of the semi-industrialized economy - FitzGerald, E (Macmillan Press in association with the Institute of Social Studies, 1993)
Presents an analysis of the semi-industrialized economy based on the work of Michal Kalecki. Discusses Kalecki and the finance of the semi-industrialized economy; the structural approach to the semi-industrialized economy; the macroeconomics of the semi-industrialized economy as implied by Kalecki in his writing on developed industrial economies; the analytics of stabilization policy; employment and the public investment criterion; financing growth in the mixed economy; planning for sectoral balance at the periphery; and state accumulation and the market. FitzGerald is Professor of Development Economics at the Institute of Social Studies, the Hague. Bibliography; index.